Safety culture in high-speed railways and the importance of top management decisions - Nikhil Bugalia; Yu Maemura; Kazumasa Ozawa (Asian Development Bank Institute (ADBI), 2019)
Safety is a central issue that challenges decision-makers during the planning and implementation of high-speed railways (HSR) and appropriate systems should be in place to ensure safe performance during operations. To contribute toward the capacity-building efforts in countries importing HSR technology, the present study aims to highlight the importance of a rather rarely discussed but inarguably essential factor, i.e., the role of top management in improving the safety culture of organizations. The present study adopts a multi-dimensional dynamic framework to assess the present state of the safety culture at two railway companies - Indian Railways (IR) and the East Japan Railway Company. Interviews with senior officials from the two organizations were conducted to assess the current state of their safety cultures using the adopted framework consisting of 11 tangible and seven intangible aspects of safety culture categorized into five levels. The aim is to develop temporal profiles of the safety culture for each organization and to reveal the underlying dynamics and associated challenges in changing the safety culture. However, preliminary results highlighting the current state of the safety culture for the two organizations, when juxtaposed, reveals opportunities for improvement for IR. Detailed discussions using examples obtained from the interviews are then used to illustrate the importance of sustained efforts from top leadership in developing a positive safety culture. The paper concludes that dynamics related to safety culture are also affected by other components of the system such as organizational structure, training system etc. Hence, an integrated approach considering the dynamic interactions between technology, human resources, management, and safety culture is deemed necessary to both analyze the current safety performance and design new management policies.
Keywords: R41; M16; 330; high-speed rail; safety management; safety culture; India; Japan; system thinking; role of leadership